Matematyka
maart
13

Poproszę o zrobienie tych zadań ;)   1. Rozwiąż równania 1) -8(x+2)+3(x+5)=-2(2x+3)+4(2x-1) 2) 6(4-x)+5(2x-5)=4(x-1)-3)(4-x)   3) (4-2x)-(x+3)=(x-5)+(-3-x) 4) (3-2x)+(3x+4)=-(3-2x)+(5x+4) 5) -(x+3)+(2x-1)=(1+4x)+(3+x) 6) -(x+3)-(2x+8)=(-3-2x)+(2x+1)   7) (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7) 8) (4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7) 9) (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6) 10) -(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)

+1
(2) Odpowiedź
wiokomada

1) -8(x+2)+3(x+5)=-2(2x+3)+4(2x-1) -8x-16+3x+15=-4x-6+8x-4 -5x-1=4x-10 -9x=-9 //:(-9) x=1   2) 6(4-x)+5(2x-5)=4(x-1)-3)(4-x) 24-6x+10x-25=4x-4-12+3x 4x-1=7x-16 -3x=-15 //:(-3) x=5   3) (4-2x)-(x+3)=(x-5)+(-3-x) 4-2x-x-3=x-5-3-x -3x+1=-8 -3x=-9 //:(-3) x=3   4) (3-2x)+(3x+4)=-(3-2x)+(5x+4) 3-2x+3x+4=-3+2x+5x+4 x+7=7x+1 -6x=-6 //:(-6) x=1   5) -(x+3)+(2x-1)=(1+4x)+(3+x) -x-3+2x-1=1+4x+3+x x-4=5x+4 -4x=8 //:(-4) x=-2   6) -(x+3)-(2x+8)=(-3-2x)+(2x+1) -x-3-2x-8=-3-2x+2x+1 -3x-11=-2 -3x=9 //:(-3) x=-3   7) (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7) 3-2x-x-4-2x-5=3x-4-5x-7 -5x-6=-2x-11 -3x=-5 //:(-3) [latex]x=\frac{5}{3}=1\frac{2}{3}[/latex]   8) (4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7) 4-x-2x-3+x-4=-2x+3-x-7 -2x-3=-3x-4 x=-1   9) (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6) 4x-5+x-7-2x+8=-3x+4-x+6 3x-4=-4x+10 7x=14 //:7 x=2   10) -(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x) -4+2x-2x-4=3x-1+2x-5-7+3x -8=8x-13 -8x=-5 //:(-8) [latex]x=\frac{5}{8}[/latex]            

nikola9848

1. -8(x+2)+3(x+5) = -2(2x+3)+4(2x-1) -8x-16+3x+15 = -4x-6+8x-4 -5x-1 = 4x-10 -5x-4x = -10+1 -9x = -9 |:(-9) x = 1   2. 6(4-x)+5(2x-5) = 4(x-1)-3(4-x) 24-6x+10x-25 = 4x-4-12+3x 4x-1 = 7x-16 4x-7x = -16+1 -3x = -15 |:(-3) x = 5   3. (4-2x)-(x+3) = (x-5)+(-3-x) 4-2x-x-3 = x-5-3-x -3x+1 = -8 -3x = -8-1 -3x = -9 |:(-3) x = 3   4. (3-2x)+(3x+4) = -(3-2x)+(5x+4) 3-2x+3x+4 = -3+2x+5x+4 x+7 = 7x+1 x-7x = 1-7 -6x = -6 |:(-6) x = 1   5. -(x+3)+(2x-1) = (1+4x)+(3+x) -x-3+2x-1 = 1+4x+3+x x-4 = 5x+4 x-5x = 4+4 -4x = 8 |:(-4) x = -2   6. -(x+3)-(2x+8) = (-3-2x)+(2x+1) -x-3-2x-8 = -3-2x+2x+1 -3x-11 = -2 -3x = -2+11 -3x = 9 |:(-3) x = -3   7. (3-2x)-(x+4)-(2x+5) = (3x-4)-(5x+7) 3-2x-x-4-2x-5 = 3x-4-5x-7 -5x-6 = -2x-11 -5x+2x = -11+6 -3x = -5 |:(-3) x = 1i2/3   8. (4-x)-(2x+3)+(x-4) = -(2x-3)-(x+7) 4-x-2x-3+x-4 = -2x+3-x-7 -2x-3 = -3x-4 -2x+3x = -4+3 x = -1   9. (4x-5)+(x-7)-(2x-8) = (-3x+4)-(x-6) 4x-5+x-7-2x+8 = -3x+4-x+6 3x-4 = -4x+10 3x+4x = 10+4 7x = 14 |:7 x = 2   10. -(4-2x)-(2x+4) = (3x-1)+(2x-5)-(7-3x) -4+2x-2x-4 = 3x-1+2x-5-7+3x -8 = 8x-13 8x = -8+13 8x = 5 |:8 x = 5/8

Dodaj swoją odpowiedź